Influence of selected phases of the menstrual cycle on performance in Special judo fitness test and Wingate test - Stefanovsky, M.; Paterova, A.; Vanderka, M.; Lengvarsky, L. (Acta Gymnica, 2016)
Background: Several scientific papers in recent years dealt with the menstrual cycle and its impact on female sport performance. No differences have been found in aerobic performance, but the results of the studies dealing with the influence of the menstrual cycle on anaerobic performance are often controversial.